Neovascular age-related macular degeneration: 18-month outcomes of aflibercept treatment in patients resistant to ranibizumab - Ertan, Elif; Doğan, Mustafa (The European Research Journal, 2019)
Objectives: Aim of this study is to investigate the effect of intravitreal aflibercept therapy in an 18-month period in patients with recurrent neovascular age-related macular degeneration resistant to intravitreal ranibizumab. Methods: This is a prospective study of eyes with neovascular age-related macular degeneration switched to intravitreal aflibercept with at least 18 month of follow-up after the switch. All patients had had a minimum of 6 injections of ranibizumab before the switch. All patients received a loading dose of three intravitreal 2 mg aflibercept injections at 4-week intervals. Changes in best-corrected visual acuity, central macular thickness and the frequency of injections were compared. Results: The study included 39 patients, each with one diseased eye. The studied eyes had received an average of 10.74 ± 4.38 previous intravitreal ranibizumab injections over a period of 28.31 ± 18.08 months. During the study, an average of 6.94 ± 2.58 intravitreal aflibercept injections were given in a period of 18 months. Mean central macular thickness at baseline, before switching to aflibercept, 6, 12, and 18 months after the aflibercept injection were 327.44 ± 120.57, 354.50 ± 127.79, 290.20 ± 112.25, 311.70 ± 119.47, and 299.29 ± 98.38 μm, respectively. A significant change was found in the macular thickness measured at intervals throughout the study. However, no significant improvement was found in visual acuity after 18 month after switching to aflibercept. Conclusions: Switching from intravitreal ranibizumab, an inhibitor of vascular endothelial growth factor-A, to aflibercept, another inhibitor for such factors, has increased central macular thickness significantly without changes in visual acuity.